Location and function of hypermarkets and shopping centers in Zagreb - Lukić, Aleksandar (Dela - Oddelek za geografijo Filozofske fakultete v Ljubljani, 2004)
Paper deals with the spatial distribution, commercial structure and functions of newly built shopping centers and hypermarkets in Zagreb. Research has included mapping of all newly built shopping centers and hypermarkets, classification of their commercial and other functions according to numbers of business premises in them, and questionnaire survey conducted in three shopping centers on different locations in Zagreb. Questionnaire survey has been done in order to understand how visitors perceive shopping centers concerning their functions and urban location.
Keywords: urbana geografija; mesta; funkcije; nakupovalni centri; trgovski centri; lokacija; Zagreb